Upcycling pineapple biomass waste to produce maltodextrin through enzymatic hydrolysis - Bambang Nurhadi; Parlan M.TP; Riksfardini Annisa Ermawar; Dewi Sondari; Adi Md Sikin; Mahani; Rossi Indiarto; S. Rosalinda; Rudy Adi Saputra; Nandi Sukri; Roni Kastaman (International Journal of Food Properties)
Pineapple biomass waste (PBW), a by-product from the production of bromelain from pineapple, was used in this study to produce maltodextrin through water extraction of the starch followed by enzymatic hydrolysis. This process utilized α-amylase to break down the α-1,6 glycosidic bonds of the extracted starch. The obtained data was analyzed using the Response Surface Method (RSM) to optimize the extraction time [Formula: see text] and temperature ([Formula: see text], while the starch content ([Formula: see text]was the response variable. The optimum starch extraction was obtained after 3 h at 75[Formula: see text], resulting in a starch purity of 91.23 [Formula: see text] 0.29% and a yield of 65.72 [Formula: see text] 0.19%. Additionally, the enzymatic hydrolysis of starch was optimize and the produced maltodextrin was characterized in terms of Dextrose Equivalent (DE). The optimum hydrolysis (30 min and 0.05–0.1% [Formula: see text] of enzyme concentration) resulted in maltodextrin containing DE values ranging from 18 to 20. The obtained maltodextrin complied with the Indonesian National Standard (SNI) for industrial specification. The obtained maltodextrin had a moisture content of monolayer value ([Formula: see text]) of 4.54 g/100 g solid and an anhydrous transition temperature ([Formula: see text]) of 154.37[Formula: see text]. This research supports sustainable practices by converting pineapple processing waste into value-added maltodextrin, a product with industrial applications.